Next-Generation Sequencing in the Diagnosis of Metastatic Lesions: Reclassification of a Glioblastoma as an Endometrial Cancer Metastasis to the Brain. (26th August 2021) - Leung, Shuk On Annie; Foley, Olivia; Chapel, David; Da Silva, Annacarolina; Nucci, Marisa; Muto, Michael G.; Campos, Susana
Abstract : : Endometrial cancer is the most common gynecologic cancer in the U.S., but metastasis to the brain is rare, and diagnosis can be challenging. Traditional tools for determining if a tumor is a primary or metastatic lesion include pan-imaging, histopathologic studies, and immunohistochemistry. Molecular testing with next-generation sequencing has been increasingly used to augment these tests. We present a case of a patient who initially presented with a brain lesion diagnosed as glioblastoma on histology and immunohistochemistry, but whose diagnosis was later changed to metastasis from an endometrial primary based on molecular findings. The two tumors shared a common microsatellite instability signature and 51 DNA variants, including oncogenic driver mutations KRAS p.G13D, PIK3CA p.E545A, and PTEN p.I135V and p.K267Rfs*9. This highlights the power of molecular analysis in making the diagnosis in cases of rare metastases. Key Points : Brain metastasis from endometrial primary is rare, and histopathological features may be augmented with molecular analysis to aid in diagnosis. Comparison of the molecular makeup of the primary endometrial lesion with the metastatic lesion may reveal high-risk molecular features that may be indicative of metastatic potential. Abstract : Metastasis of endometrial cancer to the brain is rare, and diagnosis can be challenging. This case report highlights the power of molecular analysis in making the diagnosis in cases of rare metastases.